Implementasi Problem Based Learning (PBL) Berbasis Pendekatan Berdiferensiasi dalam Upaya Peningkatkan Hasil Belajar Materi Rantai Makanan Peserta Didik Kelas V - Amalia, Leny; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The background to this research is the problems found in class V in science and science learning about food chains. Based on the results of observations of the science and science learning process in class V, students found problems or difficulties regarding food chain material, namely related to determining consumers I, II, and so on. In this way, a problem-based learning model was chosen which has the advantage of being appropriate to students' real lives, as well as a differentiated approach which adapts to students' needs. The aim of this research is to describe the implementation of a problem based learning model based on a differentiated approach in improving the learning outcomes of class V students on food chain material at SD Negeri Kandangan 04. This type of research is descriptive qualitative with test collection techniques in the form of pretest and posttest and non-tests in the form of observation and documentation. This research was conducted at SD Negeri Kandangan 04 with the subject of class V students with a total of 22 students and class V teachers. The results of the research show that the implementation of a problem based learning model based on a differentiated approach can improve student learning outcomes. This is proven by the average percentage increase of 16.62% and the increase in the number of students who completed the posttest after implementing the problem based learning model based on a differentiated approach in science and science learning in class V on food chain material. Thus, the implementation of problem based learning based on a differentiated approach in food chain material can improve the learning outcomes of class V students at SD Negeri Kandangan 04.